PENERAPAN EKONOMI DIGITAL DALAM MENINGKATKAN PENDAPATAN PELAKU UMKM KABUPATEN REJANG LEBONG: PENERAPAN EKONOMI DIGITAL DALAM MENINGKATKAN PENDAPATAN PELAKU UMKM KABUPATEN REJANG LEBONG - Silvia, Sineba Arli; Soleha, Soleha (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2022)
The rapid development of technology in the digital era has driven changes in payment transactions. Payments currently no longer use cash in cash but use digital payments. This change is strongly driven because of the ongoing pandemic, so the presence of digital payment transactions is very helpful in increasing the income of micro, small and medium enterprises (MSMEs). QR code is a payment system that is used to facilitate transactions so as to increase the income of business people so they don't miss out. This study aims to determine the application of the digital economy of MSME business actors in Curup City. This type of research is a field research research. Data collection techniques using observation and interviews. The results of the study indicate that the application of the digital economy used by MSME business actors in Curup City has been running and growing rapidly. The existence of applications, websites, social media and others are very helpful and facilitate business activities. Some payment applications that we are familiar with are QR, Shopeepay, Ovo, Dana, Link Aja, Grab, Gojek and so on. The most widely used application is QR scan barcode. Many benefits are obtained not only for consumers, the benefits are also felt by MSME business people. The changes that are felt after using digital payment transactions are the most important, namely increasing income, making it easier to carry out promotions, reducing production costs, increasing sales, avoiding direct contact with money so as to reduce the spread of COVID-19.